How normalization can be linked with theory of planned behavior towards the actual behavior of green practice on mobile phone - Wong, Ling Chai; Oswald @ Aisat Igau; Stephen Laison Sondoh Jr (2018)
The evolution of mobile phones into smart multi-functional mobile computers have led to a serious Abnormal Battery Drain (ABD) issue. This has spurred the need for green practice in mobile phone to overcome ABD concern. However, far too little attention has been paid to the green practice that focuses on ABD. Hence, this paper aims to conceptualize the actual behavior of green practice on mobile phones by integrating the Theory of Planned Behavior and Normalization Process Theory. Previous studies have found that current green marketing has failed to predict the actual green practice; the intention does not come with actual behavior. Actual green practice only can be achieved through normalization of green practice across the board. Therefore, normalization is strongly suggested to be integrated with the Theory of Planned Behavior to ensure the actual behavior in green practice can be achieved. Apart from conceptualization, the paper also proposes a total of 400 self-administered questionnaires to be distributed among mobile phone users, in main cities in Malaysia via a snowball sampling technique. The Partial Least Square-Structural Equation Modelling (PLS-SEM) approach has been used for data analysis. The final section of this paper involves a discussion of the findings and limitations of the study.